Composição de fibras musculares esqueléticas de eqüinos jovens da raça Brasileiro de Hipismo - D Angelis, F.H.F.; Martins, C.B. [UNESP]; Silva, M.A.G. [UNESP]; Oliveira, J.V.; Boleli, I.C. [UNESP]; Lacerda-Neto, J.C. [UNESP]; Queiroz- Neto, A. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2006)
The aim of this study was to typify the skeletal striated fibers of the gluteus medius muscle of young Brasileiro de Hipismo (BH) horses by means of histochemical analysis with m-ATPase and NADH-TR according to the sex and the biopsy depth. It was observed that the frequency (F;%) and the relative cross sectional area (RCSA;%) of the fibers type IIX were greater than the fibers type IIA, which F and RCSA were greater than the fibers type I. The comparison between sex and muscles depht, showed no significant difference in F and RCSA in the three types of fibers. The results of morphometry showed that the gluteus medius muscle has greater glycolitic metabolism and anaerobic capacity because of the presence of large proportion of type IIX fibers. This may be justified by the genetic influence of Thoroughbred in the formation of Brasileiro de Hipismo breed.
Composition of skeletal muscle fibers of young Brasileiro de Hipismo horse breed
Keywords: Equine; Brasileiro de Hipismo breed; muscle biopsy; histochemistry; Equino; Brasileiro de Hipismo; Biópsia muscular; Histoquímica